About the location of some quasipolinomial roots - Donatas Švitra; Ingrida Sirvydaitė (Lietuvos Matematikos Rinkinys)
The location of quasipolinomial roots in a complex plane that appear while we investigate differential equations of the locator and the combustion process in the rocket engine is analysed. The same research is carried out for a differential equation with delay of neutral type appearing in mathematical ecology.